O-15 An exercise and nutritional rehabilitation (ENeRgy) trial in patients with incurable cancer. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Hall, Charlie; Cook, Jane; Blackwood, Honor; Haraldsdottir, Erna; Brown, Duncan; Maddocks, Matthew; Dixon, Liz; Skipworth, Richard; Fallon, Marie; Laird, Barry
Abstract : Background: Rehabilitation is an essential component of palliative care (Tiberini & Richardson, 2015), however, data on efficacy and key components are lacking (Salakari, Surakka, Nurminen et al ., 2015). There is a strong argument that any rehabilitation programme should combine exercise and nutrition, which together may improve physical function and quality of life, but this needs careful evaluation (Payne, Larkin, McIlfatrick, et al ., 2013; Chasen, Bhargava, MacDonald, 2014). This is being done through the ENeRgy trial which compares an Exercise and Nutrition based Rehabilitation programme with standard care, in patients with incurable cancer. The trial was funded by Marie Curie and the Chief Scientist Office. Aims: The primary aim was to assess the feasibility of an Exercise and Nutrition based Rehabilitation programme. Secondary aims included assessment of quality of life (patient and partner-carers), functional and nutritional status, contamination of the control group, health economic impact and survival. Methods: A single centre, randomised, unblinded feasibility trial was undertaken. Patients were randomised to receive an exercise and nutrition based rehabilitation programme (intervention) or standard care (control). Eligible patients were: ≥18 years, Karnofsky Performance Status ≥60, with a diagnosis of incurable cancer; not undergoing anti-cancer treatment. Results: 45 patients were recruited from a mixture of hospices and a cancer centre. Challenges included optimising patient recruitment, compliance with the components of the rehabilitation programme, and the establishment of a clinical research team within an independent hospice. Patients' overall experience of the rehabilitation trial was positive and nurtured a positive, empowering impression of the hospice setting. Key themes and some preliminary data will be presented. Conclusions: The ENeRgy trial is an important step in assessing the feasibility of an outpatient, hospice based rehabilitation programme for patients with incurable cancer and will inform future work in this area.